Observation of Microstructure Formation During Freeze-Drying of Dextrin Solution by in-situ X-ray Computed Tomography - Nakagawa, Kyuya; Tamiya, Shinri; Sakamoto, Shu; Do, Gabsoo; Kono, Shinji (Frontiers in Chemistry, 2018)
In-situ X-ray computed tomography (CT) technique was used to observe microstructure formations during freeze-drying of dextrin solution. A specially designed freeze-drying stage was equipped at the X-ray CT stage, and the frozen and dried microstructures were successfully observed. The CT images of the frozen solution clarified the ice crystal size increase and the obvious boundary formation between the ice and freeze-concentrated phases when applying post-freezing annealing at –5ºC. These structural modifications were due to the Ostwald ripening and glassy phase relaxation. During freeze-drying, the pore microstructures formed as a consequence of the water removal. The pores were the replicas of the original ice microstructures, whereas some pore microstructures newly formed by the removal of water. This later mechanism was obvious in the non-annealed sample than in the annealed sample. The glassy phase in the non-annealed solution was not perfectly freeze-concentrated, so water was rapidly removed from this phase and lost its original microstructure. At this moment, the freeze-concentrated region should be piled up to the brand-new pore walls, this consequently thickened pore walls. Image analysis estimated that the mean pore wall thickness for the non-annealed and annealed samples were 13.5 and 8.6 µm, respectively. It was suggested that the advantages of annealing are not only to reduce drying time due to the modification of ice crystal morphologies but also to avoid quality loss that relate to the structural deformation of the glassy matters.